Respon Pertumbuhan Dan Hasil Tanaman Cabai Keriting Akibat Pemberian Jenis Dan Dosis Pupuk Kandang Yang Berbeda - Luthfi Muthiara Putri; Selvy Isnaeni; R. Arif Malik Ramadhan (Universitas Wiralodra, 2026)
The problem of land degradation and the high price of inorganic fertilizers are factors that cause the production of curly chilies to be less than optimal. One effort to overcome this is the use of organic fertilizers such as chicken, cow, and goat manure as a source of nutrition for plants. This study aims to determine which type and dose of manure is optimal for the growth and yield of cayenne pepper plants. The study was conducted in Purwaharja Village, Purwaharja City, Banjar City, West Java from September 2024 to January 2025. This study used a factorial Randomized Block Design (RAK). The first factor is the type of manure consisting of 6 levels including K1 (chicken manure), K2 (cow manure), K3 (goat manure), K4 (chicken + cow manure), K5 (chicken + goat manure), and K6 (cow + goat manure). The second factor is the dose of manure consisting of 3 levels including D1 (150 g polybag-1), D2 (200 g polybag-1), and D3 (250 g polybag-1). The type of chicken and goat manure is optimal for plant height (60.53 cm) and number of leaves (44 strands), the type of chicken, goat, chicken + cow, chicken + goat, cow + goat manure is optimal for leaf color 4 MST (4), and the type of chicken manure is optimal for the beginning of flowering (36 HST). The dose of manure is 250 g polybag-1 optimal for plant height (49.41 cm), number of leaves (55 strands), and leaf color 4 MST (4), and a dose of 200 g polybag-1 optimal for leaf color 4 MST (4). There is an interaction between the treatment of type and dose of manure on leaf color 8 MST.